Growing Business Entrepreneurs And Enhancing The Competitiveness Of Community SME’s Productsof Hendrosari Village, Menganti District, Gresik Regency - beni komara; Heri Cahyo Bagus Setiawan; Muhammad Ghufran Ramdhani; Ragillia Ragillia (OJS Universitas Muhammadiyah Gresik, 2020)
Lontar Tourism Village, Hendrosari Village, Menganti Subdistrict, Gresik Regency is located in the range of 15 Km from the center of Gresik. The locals are very creative by continuing their culinary innovations besides Legen and dawet siwalan to the grilled chicken menu as a companion. The community's huge interest in the typical culinary of Hendrosari Village is then continued with the development of the tourist village of Lontar Sewu Nature & Culinary Tourism Village. There is a jogging track built to cross the palm plantations, a traditional culinary center of Gresik and a tourist attraction for game rides and a great place for selfies. Physically, the development of the tourism village has been completed and began to operate, but there are still many stakeholders, especially the main activists of the Tourism Village and the community still need guidance as to how they are able to optimize the potential of the tourist village in their place through entrepreneurship. How to take the right steps so that the local wisdom of this tourism village is able to significantly strengthen the superiority of the product which is expected to be able to raise economic independence in the village of Hendrosari. This problem then became the basis of the Community Partnership Program (PKM) in Hendrosari village. Through this program, the main activists of the Tourism Village consisting of Bumdes, PKK cadres, Karang Taruna cadres and the Tourism Village Activity Organizing Committee and the community will be given a briefing to foster entrepreneurial spirit enhancing the competitiveness of MSME products, the Lontar Tourism Village, Hendrosari Village, Menganti District, Gresik Regency . The purpose of carrying out PKM activities are; 1. Growing the entrepreneurial spirit of the community of Hendrosari village 2. Increasing the product competitiveness of the community of the village of Hendrosari. The method used is the lecture and discussion method, technology transfer and demonstration method. Through coaching in the PKM program, it is expected that the main activists in the Tourism Village and the community will be able to foster an entrepreneurial spirit and be able to increase the competitiveness of the MSME products of the Lontar Tourism village community, Hendrosari Village, Menganti District, Gresik Regency.